Paper-based molecularly imprinted film designs for sensing human serum albumin - Tzu-Chieh Lin; Chung-Yin Lin; Yi-Ting Hwang; Dar-Fu Tai (Talanta Open)
A general, simple, and inexpensive method for fast and high throughput that monitors target model proteins and the sequential incorporation of functional monomers were presented for the preparation of molecularly imprinted films (MIFs) on cellulose filter papers (MIFPs). Owing to the inaccessibility of the fatty acid binding sites on human serum albumin (HSA), four classified-segment peptides with different chain lengths (i.e., HSA112–122, HSA302–313, HSA500–511, and HSA568–582) were selected and tested with regard to both MIFPs enrichment and fluorescent detection. The novel HSA MIFPs that designed for this study involve a monomer crosslinker instead of the commonly used crosslinker. Imprinted cavities took shape in different solvent systems on MIFPs because the conformation of the template peptide is fixed. When the solvent system changed to a 70% 2,2,2-trifluoroethanol (TFE) solution, the conformation of the peptide chains changed from an extended coil structure to a helix structure. Therefore, the film bound to the mother protein selectively. The imprinting conditions were optimized while the binding affinity, adsorption kinetics, and selectivity of the MIFPs for each template peptide were also evaluated. Fluorescence assays led to generate Scatchard plots revealing that, for MIFP568−582Helix, HSA had a dissociation constant (Kd) of 4.8 μM and a maximum bind capacity (Bmax) of 0.5604 nmole. The binding selectivity was 10-folds more sensitive than MIFP568−582Randomcoil. As for the MIFP568−582Helix response time was found to be 5 min. In short, a combined fluorescent platform could be used to monitor and capture proteins conveniently, inexpensively, quickly, and accurately detect without the need of too much professional input.